Factors determining antenatal care utilization among mothers of deceased perinates in Ethiopia - Tesfay, Neamin; Kebede, Mandefro; Asamene, Negga; Tadesse, Muse; Begna, Dumesa; Woldeyohannes, Fitsum (Frontiers in Medicine, 2023)
Receiving adequate antenatal care (ANC) had an integral role in improving maternal and child health outcomes. However, several factors influence the utilization of ANC from the individual level up to the community level factors. Thus, this study aims to investigate factors that determine ANC service utilization among mothers of deceased perinate using the proper count regression model.Secondary data analysis was performed on perinatal death surveillance data. A total of 3814 mothers of deceased perinates were included in this study. Hurdle Poisson regression with a random intercept at both count-and zero-part (MHPR.ERE) model was selected as a best-fitted model. The result of the model was presented in two ways, the first part of the count segment of the model was presented using the incidence rate ratio (IRR), while the zero parts of the model utilized the adjusted odds ratio (AOR).This study revealed that 33.0% of mothers of deceased perinates had four ANC visits. Being in advanced maternal age [IRR=1.03;95CI:(1.01-1.09)], attending primary level education [IRR=1.08;95CI:(1.02-1.15)], having an advanced education (secondary and above) [IRR=1.14;95CI:(1.07-1.21)] and being resident of a city administration [IRR=1.17;95CI:(1.05-1.31)] were associated with a significantly higher frequency of ANC visits. On the other hand, women with secondary and above education [AOR=0.37;95CI:(0.26-0.53)] and women who live in urban areas [AOR=0.42;95CI:(0.33-0.54)] were less likely to have unbooked ANC visit, while women who resided in pastoralist regions [AOR=2.63;95CI:(1.02-6.81)] were more likely to have no ANC visit.The uptake of ANC service among mothers having a deceased perinate was determined by both individual (maternal age and educational status) and community (residence and type of region) level factors. Thus, a concerted effort is needed to improve community awareness through various means of communication by targeting younger women. Furthermore, efforts should be intensified to narrow down inequalities observed in ANC service provision due to the residence of the mothers by availing necessary personnel and improving the accessibility of service in rural areas.